Mechanisms for governing the water-land-food nexus in the lower Awash River Basin, Ethiopia: Ensuring policy coherence in the implementation of the 2030 Agenda - Srinivasa Reddy Srigiri; Anita Breuer; Waltina Scheumann (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Interdependencies among the goals and targets make the 2030 Agenda indivisible and their integrated implementation requires coherent policies. Coordination across different sectors and levels is deemed as crucial for avoiding trade-offs and achieving synergies among multiple, interlinked policy goals, which depend on natural resources. However, there is insufficient evidence regarding the conditions under which coordination for integrated achievement of different water- and land-based Sustainable Development Goals (SDGs) functions effectively. The paper investigates the land and water governance in the Ethiopian lower Awash River basin and identifies key interdependencies among related SDGs. It assesses in how far the interactions and coordination among various decision-making centres are effective in managing the interdependencies among different goals. Systems for using and managing water and land exhibit features of polycentric governance as this process involves decision-making centres across different sectors and at various levels. Key action situations for land and water governance in operational, collective and constitutional choice levels are interlinked/networked. Each action situation constitutes actions that deliver one of the functions of polycentric governance, such as production, provision, monitoring etc. as an outcome, which affects the choices of actors in an adjacent action situation. The study shows that the existing institutions and governance mechanisms for water and land in Ethiopia are not effective in managing the interdependencies. Non-recognition of traditional communal rights of pastoralists over land and water and ineffective policy instruments for ensuring environmental and social safeguards are leading to major trade-offs among goals of local food security and economic growth. The autocratic regime of Ethiopia has coordination mechanisms in place, which fulfil the role of dissemination of policies and raising awareness. However, they are not designed to build consensus and political will for designing and implementing national plans, by including the interests and aspirations of the local communities and local governments. The study recommends efforts to achieve SDGs in the Ethiopian Awash River basin to focus on strengthening the capacities of relevant actors, especially the district and river basin authorities in delivering the key governance functions such as water infrastructure maintenance, efficient use of water, and effective implementation of Environmental Impact Assessment (EIA). Further, urgent efforts for scaling up of recognition, certification and protection of communal land rights of pastoralists and clear definition of rules for awarding compensation upon expropriation, are required.
Keywords: 330